Medaka (Oryzias latipes) initiate courtship and spawning late at night: Insights from field observations - Yuki Kondo; Kotori Okamoto; Yuto Kitamukai; Yasunori Koya; Satoshi Awata (PLoS ONE, 2025)
Laboratory experiments were conducted using model organisms to elucidate biological phenomena. However, the natural habitats of organisms are inherently more complex than those found in the laboratory. To complement the laboratory experiments, we conducted field observations of the small freshwater fish medaka (Oryzias latipes), widely used as a model organism, to elucidate its ecology and behavior in natural environments. Our results showed that medaka initiated courtship and spawning late at night, much earlier than previously thought. Nocturnal video observations examining spawning time during the breeding season in Gifu, Japan (sunset: 19:00; sunrise: 5:00) revealed the presence of post-spawning medaka females around midnight. Behavioral analysis showed that the medaka was inactive until 23:00, with activity increasing from 0:00 and peaking from 1:00 to 3:00. Furthermore, a significant increase in male courtship was observed between 0:00 and 4:00. These findings provide the first empirical evidence that medaka mating begins significantly earlier than previously reported in the laboratory, as within an hour before or after light onset in the morning. This study highlights the importance of field observations in revealing critical aspects of organismal biology that may be overlooked in laboratory settings.